Not form, not genre, but style: on literary categories. Issue 4 (3rd April 2022) - Dango, Michael
ABSTRACT: This metacritical essay compares three concepts in literary criticism – form, genre, and style – each of which lumps together disparate objects in a common category. Lumping is an essential component of what we as humanists ought to be in the business of doing, and this essay defends the taxonomic impulse. But I argue that different categories produce different kinds of knowledge; and that for contemporary literary criticism, we need stylistic knowledge more than formal or generic. I theorise genres as affective institutions, which provides more leverage than formalism does in tracking the ongoing modulation of social structure in the historical present. And yet genre can still only get us so far, which is why we need a rejuvenated theory of style. Drawing but departing from recent critical accounts of style including Mark McGurl and D. A. Miller, I theorise style as action, not an expression of affect, and as a coordination of form and content. If form attends more to structure, and genre attends more to affect, then style attends to their entanglement, highlighting strategies developed to adapt to the affective pressures of social structure.